Systematic optimization of visible light-induced crosslinking conditions of gelatin methacryloyl (GelMA) - Sina Sharifi (Nature Portfolio, 2021)
Abstract Gelatin methacryloyl (GelMA) is one of the most widely used photo-crosslinkable biopolymers in tissue engineering. In in presence of an appropriate photoinitiator, the light activation triggers the crosslinking process, which provides shape fidelity and stability at physiological temperature. Although ultraviolet (UV) has been extensively explored for photo-crosslinking, its application has been linked to numerous biosafety concerns, originated from UV phototoxicity. Eosin Y, in combination with TEOA and VC, is a biosafe photoinitiation system that can be activated via visible light instead of UV and bypasses those biosafety concerns; however, the crosslinking system needs fine-tuning and optimization. In order to systematically optimize the crosslinking conditions, we herein independently varied the concentrations of Eosin Y [(EY)], triethanolamine (TEOA), vinyl caprolactam (VC), GelMA precursor, and crosslinking times and assessed the effect of those parameters on the properties the hydrogel. Our data showed that except EY, which exhibited an optimal concentration (~ 0.05 mM), increasing [TEOA], [VA], [GelMA], or crosslinking time improved mechanical (tensile strength/modulus and compressive modulus), adhesion (lap shear strength), swelling, biodegradation properties of the hydrogel. However, increasing the concentrations of crosslinking reagents ([TEOA], [VA], [GelMA]) reduced cell viability in 3-dimensional (3D) cell culture. This study enabled us to optimize the crosslinking conditions to improve the properties of the GelMA hydrogel and to generate a library of hydrogels with defined properties essential for different biomedical applications.